Digital Leadership, Psychological Empowerment, and Organizational Citizenship Behavior in Private Universities: The Mediating Role of Work Engagement - Khitara Aldilla Chandra; Silfia Silfia (JURNAL PELITA MANAJEMEN, 2026)
This study examines the effects of digital leadership and psychological empowerment on Organizational Citizenship Behavior, with work engagement as a mediating variable among administrative staff in private universities. A quantitative approach with an explanatory survey design was employed. Data were collected from 214 permanent administrative staff members from seven medium-sized private universities in the Greater Bandung area using a structured questionnaire. The data were analyzed using descriptive statistics, validity and reliability testing, correlation analysis, path analysis, and mediation testing. The findings show that digital leadership and psychological empowerment have positive and significant effects on Organizational Citizenship Behavior. Work engagement also has the strongest direct effect on Organizational Citizenship Behavior and partially mediates the effects of digital leadership and psychological empowerment. These results indicate that voluntary behavior among administrative staff is strengthened when digital leadership and psychological empowerment are supported by high work engagement. This study contributes to organizational behavior and higher education management literature by offering an integrated model for explaining Organizational Citizenship Behavior in private university administration.